A Methodology for Spatial Domain Image Compression Based on Hops Encoding. (2016) - George, Maria; Thomas, Manju; Jayadas, C.K.
Abstract: Spatial Domain Image Compression based on Hops Encoding is an efficient algorithm that exploits the encoding of the error between the predicted value and pixel value. For all images a constant set of hops are derived and can be used at both encoder and decoder. The main advantage of hops encoding is that the method is made simple and high quality results in terms of Peak Signal-to-Noise Ratio (PSNR), image quality metrics with full-reference Feature SIMilarity index(FSIM) and non-reference Blind/Reference-less Image Spatial QUality Evaluator (BRISQUE). The constant array of hops is derived from analysis of sample images. Hops encoder outperforms LHE, JPEG and JPEG2000 at low bitrates.